EDITORIAL - Surichaqui Gutiérrez, Franklin (2021)
The Scientific Journal Engineering Sciences is sponsored by the Professional School of Civil Engineering-Lircay of the National University of Huancavelica, has the honor to present to the university community and society in general, as it contains original and unpublished articles of scientific research with engineering as an objective theme with a thematic coverage in the fields of basic and applied branches of engineering.The Scientific Journal Engineering Sciences encourages the promotion of innovative and technological research in order to strengthen research skills in young engineering students and professionals in the region of Huancavelica, as well as nationally and internationally.We urge not to lose heart in our efforts to create new knowledge that generates positive impacts in the promotion of a better quality of life for our society. Translated with www.DeepL.com/Translator (free version)